Digital economy, transfer of agricultural labor force and agricultural land production efficiency - Liuyan Li; Manman Qu (Frontiers in Environmental Science, 2025)
The digital economy has emerged as a new driving force and engine for China’s economic growth. However, given the current shortage of production factors, whether the digital economy positively impacts agricultural land productivity remains to be further confirmed. This study employs balanced panel data from 31 Chinese provinces between 2009 and 2023, constructs a three-tier indicator framework, and measures China’s digital economy development level using the entropy method. The research explores the impact and mechanisms of the digital economy on agricultural productivity. Key findings include: (1) Bidirectional fixed-effects models demonstrate that the digital economy significantly enhances agricultural productivity, supported by endogeneity tests, robustness checks, and threshold analysis. (2) Heterogeneity analysis reveals stronger productivity improvements in eastern, central, and northeastern regions, particularly in major grain-producing areas. (3) Mediation tests confirm that the digital economy boosts agricultural productivity by facilitating labor mobility. Based on these conclusions, policy recommendations are proposed: fundamentally improving rural digital infrastructure, establishing region-specific development frameworks, and strengthening support for digital agriculture entities. These measures provide practical pathways to enhance agricultural productivity.